2021
DOI: 10.3389/fnut.2021.773064
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Shrimp Peptide on Dextran Sulfate Sodium-Induced Colitis in Mice

Abstract: Inflammatory bowel disease, an intestinal relapsing inflammatory disease, not only impairs gastrointestinal function but also increases the chances of developing colon cancer. Currently, the effects of shrimp peptide (SP) in mice model of ulcerative colitis (UC) are still unclear. In particular, it is uncertain whether SP affects the gut flora with UC mice. In this study, we investigated the anti-inflammatory effects of SP on a dextran sulfate sodium (DSS)-induced mouse model of UC. Firstly, the molecular weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 46 publications
0
9
1
Order By: Relevance
“…58 IL-6 was significantly increased in mice with DSS-induced colitis, which might be involved in the regulation of signaling pathways such as apoptosis, migration, and protein synthesis. 59 In the present study, TSCHs could decrease the content wileyonlinelibrary.com/jsfa of IL-6; however, the inhibitory effect of medium dose TSCHs (500 mg kg −1 ) on IL-6 was lower than that of low dose TSCHs (250 mg mg −1 ), which may mean that TSCHs do not act in a dose-dependent manner in DSS-induced UC. Moreover, the standard error of the medium dose of TSCHs (500 mg kg −1 ) was relatively large, which may be caused by individual differences in animals.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…58 IL-6 was significantly increased in mice with DSS-induced colitis, which might be involved in the regulation of signaling pathways such as apoptosis, migration, and protein synthesis. 59 In the present study, TSCHs could decrease the content wileyonlinelibrary.com/jsfa of IL-6; however, the inhibitory effect of medium dose TSCHs (500 mg kg −1 ) on IL-6 was lower than that of low dose TSCHs (250 mg mg −1 ), which may mean that TSCHs do not act in a dose-dependent manner in DSS-induced UC. Moreover, the standard error of the medium dose of TSCHs (500 mg kg −1 ) was relatively large, which may be caused by individual differences in animals.…”
Section: Discussioncontrasting
confidence: 64%
“…NF‐κB is considered to play a key role in the release of proinflammatory mediators; it has been reported that colonic inflammation can be alleviated by inhibiting the translocation of p65 from the cytosol to the nucleus, the phosphorylation and degradation of IκB‐α, and suppression of the expressions of NF‐κB‐related proteins 58 . IL‐6 was significantly increased in mice with DSS‐induced colitis, which might be involved in the regulation of signaling pathways such as apoptosis, migration, and protein synthesis 59 . In the present study, TSCHs could decrease the content of IL‐6; however, the inhibitory effect of medium dose TSCHs (500 mg kg −1 ) on IL‐6 was lower than that of low dose TSCHs (250 mg mg −1 ), which may mean that TSCHs do not act in a dose‐dependent manner in DSS‐induced UC.…”
Section: Discussionmentioning
confidence: 99%
“…The expression levels of inflammatory factors such as TNF-α, IL-1β, and IL-6 in UC were increased by abnormal activation of the PI3K/AKT signalling pathway (Li et al 2019a , b ; Li et al 2019a , b ). Furthermore, TNF-α is an important proinflammatory cytokine involved in the pathogenesis of UC, inducing the pathological opening of the intestinal tight junction barrier, increasing intestinal epithelial permeability, and disrupting intestinal barrier function (Xiang et al 2021 ; Shin et al 2020 ). Therefore, anti-TNF-α therapy has been widely used in clinical practice as a suitable method of UC treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, OE intake could slightly restore the structure of the fecal microbiota to that observed in normal mice (control group) ( Figure 6 C). Other food components, including radish sprout [ 44 ] and shrimp peptide [ 45 ], have also been reported to improve gut bacterial diversity reduced by DSS administration. Thus, OE intake may improve α- and β-diversity, exacerbated by DSS administration.…”
Section: Discussionmentioning
confidence: 99%